Quinolone Signals Related to Pseudomonas Quinolone Signal-Quorum Sensing Inhibits the Predatory Activity of Bdellovibrio bacteriovorus - Hoshiko, Yuki; Nishiyama, Yoshito; Moriya, Tae; Kadokami, Kiwao; López-Jácome, Luis Esaú; Hirano, Ryutaro; García-Contreras, Rodolfo; Maeda, Toshinari (Frontiers in Microbiology, 2021)
Bdellovibrio bacteriovorus is one of the predatory bacteria; therefore, it can act as a novel “living antibiotic”, unlike the current antibiotics. Here, predation of Escherichia coli by B. bacteriovorus was inhibited in the presence of Pseudomonas aeruginosa. This study investigated whether P. aeruginosa-induced predation inhibition is associated with bacterial quorum sensing (QS). Each las, rhl, or pqs QS mutant in P. aeruginosa was used to check predatory activity of E. coli cells using B. bacteriovorus. Therefore, predatory activity of B. bacteriovorus increased in a mutant pqs QS system, whereas wild-type PA14 inhibited predatory activity. Moreover, the addition of 4-hydroxy-2-heptylquinoline (HHQ) or the analog triggered the low predatory activity of B. bacteriovorus and killed B. bacteriovorus cells. Therefore, a defensive action of P. aeruginosa against B. bacteriovorus is activated by the pqs QS system, which produces some quinolone compounds such as HHQ.